2022
DOI: 10.1007/s12032-022-01746-4
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-3 sponges Tiam1 to manipulate MMP-7 activity through β-catenin signaling in oral squamous cell carcinoma

Abstract: Purpose: Oral squamous cell carcinoma (named OSCC) is considered as the most frequent malignancy in oral cavity, which has became a rapid increasing problem for the global public health with unclear underling molecular mechanism. Previously, we reported Tiam1 (T-lymphoma invasion and metastasis inducing factor 1) as a potential oncogene for OSCC. Here, we in-depth explored its signaling mechanism.Methods: The mRNA and protein expression levels of primary differentially expressed genes (Tiam1, Fibulin-3 and MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Tiam1 has been reported as a potential oncogene in oral squamous cell carcinoma. In this study, Tiam1 directly interacts with Fibulin‐3 to compete for the nuclear translocation of β‐catenin, and then stimulates the expression of MMP‐7 through the interaction of TCF‐4 domain to promote EMT 139 . In addition, Chen et al 140 .…”
Section: Other Mcpsmentioning
confidence: 74%
See 1 more Smart Citation
“…Tiam1 has been reported as a potential oncogene in oral squamous cell carcinoma. In this study, Tiam1 directly interacts with Fibulin‐3 to compete for the nuclear translocation of β‐catenin, and then stimulates the expression of MMP‐7 through the interaction of TCF‐4 domain to promote EMT 139 . In addition, Chen et al 140 .…”
Section: Other Mcpsmentioning
confidence: 74%
“…In this study, Tiam1 directly interacts with Fibulin-3 to compete for the nuclear translocation of β-catenin, and then stimulates the expression of MMP-7 through the interaction of TCF-4 domain to promote EMT. 139 In addition, Chen et al 140 found that the expression of Fibulin-4 is increased in esophageal squamous cell carcinoma, and its down-regulation inhibits the proliferation, invasion and migration of cancer cells in vitro and in vivo. Inhibition of Fibulin-4 expression inhibits cell protective autophagy by activating Akt-mTOR signaling pathway, thus enhancing cell sensitivity to apatinib.…”
Section: Other Mcpsmentioning
confidence: 99%
“…The differential regulation of genes identified herein expands our understanding of hydration homeostasis as it pertains to vocal fold tissue and lays preliminary groundwork to explore the molecular basis of dehydration‐related voice changes more comprehensively. EFEMP1 , upregulated by dehydration in vocal folds, encodes Fibulin‐3 that regulates elastin stability, a major structural component of the vocal folds, and fibroblast activity in various conditions such as direct inguinal hernia, 23 cancer‐associated phenotypes, 24,25 and vascular endothelial function 26 . CLIC5 , also upregulated in the Dehydration group, is an intracellular ion channel with important pleiotropic effects on epithelial cell maintenance through interaction with the cytoskeleton 27,28 ; it was reported to contribute to the response to cardiac ischemic reperfusion 29 .…”
Section: Discussionmentioning
confidence: 99%